Exploring the Impact of Small-group Synchronous Discourse Sessions in Online Math Learning - Jinnie Choi; Alyssa Walters (Online Learning, 2019)
Students in a fully-online learning environment have limited access to opportunities to talk about math problem solving. While discourse is a promising pedagogical model, less is known about how it translates to online math learning. We analyzed online platform data from two fully-online virtual elementary schools in the United States to address the following research questions: (a) Is participating in math discourse about reasoning and problem-solving related to students’ confidence, self-efficacy toward math, and math mindset in an online learning environment? (b) Is participation in math discourse related to math performance? The results showed that (a) repeated participation in the discourse sessions in a course was not directly related with changes in confidence, self-efficacy toward math, and math mindset, and (b) higher numbers of sessions that students participated in was associated with higher performance in final math course score and state assessment results, after controlling for prior performance and confidence, self-efficacy and mindset scores.